Management skills among the health officers in Malaysia, 1999 - Noor Ashah Itam Othman,; Syed Mohamed Aljunid, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
A cross sectional study was carried out to determine the management skills and factors that influence it among health officers in Malaysia. Datas were acquired through a postal self-administrated questionnnaires .A total of 123 (51.3%) of respondents had given the feedback. Among them. 71(57.7%) had good personnel skills. 56(45.5%) had good conceptional skills. 59(48.0)% had good technical skills and 67(54.5%)had good overall management skills. Overall management skills was influenced by working place of the respondents where those who were working in the District Health Offices had been better skill then those working in Ministry of Health Headquarters. Respondents who had found good in personnel skills were those aged above 35 years. U2 .graduated from over sea. more then ten years of service and worked as Medical and Health Officer before. Those who were better in conceptional skills were aged above 35 years and who were working in District Health Offices. Those who had a good technical skills were those who worked in District Health Offices. U2 .graduated from over sea and had non management specialised .Health officers in Ministry of Health Headquarters need to be posted to District Health Offices to improve their management skills. The quality of the health management courses should be plan properly.